Development of a 12 month screener based on items from the Bayley II Scales of Infant Development for use in Low Middle Income countries. Issue 4 (April 2015) - Biasini, Fred J.; De Jong, Desiree; Ryan, Sarah; Thorsten, Vanessa; Bann, Carla; Bellad, Roopa; Mahantshetti, Niranjana S.; Dhaded, Sangappa M.; Pasha, Omrana; Chomba, Elwyn; Goudar, Shivaprasad S.; Carlo, Waldemar A.; et al.
Abstract: Objectives: The purpose of the current study was to adapt the Bayley Scales of Infant Development II for use as a screening measure that could be used by health care professionals in Low Middle Income (LMI) countries with 12 month old infants to determine if they needed further assessment and early intervention. Methods: The adaptations were made as part of a larger study of children participating in a home-based early intervention program in India, Pakistan, and Zambia. Using Item Response Theory, a brief 12 month screener, with excellent sensitivity and specificity was identified. Results: The proposed 12 month screener contains 7 mental/cognitive items and 5 motor items. Children who cannot perform more than 3 items on the mental scale (sensitivity 79%, specificity 85%) and/or 3 items on the motor scale (sensitivity 96%, specificity 95%) should be referred for further assessment. Conclusion: This screener can reliably be used to determine if a child needs further developmental assessment. Highlights: There is a need for objective screening measures to identify infants at-risk for developmental delays in various cultures. Early detection of developmental delays leading to intervention can improve quality of life. We developed a 12 month screener using items from the Bayley Scales II for use in Low Middle Income countries. The proposed 12 month screener contains 7 mental/cognitive items and 5 motor items. The screener can reliably be used to determine if a child needs further developmental assessment.